Antioxidant potential of tree bark extracts: Insight from the multi-level output of the Antioxidant Power 1 assay - Johanna Rehrl; Thomas Sepperer; Sissy Häsler Gunnarsdottir; Thomas Schnabel; Gertie Janneke Oostingh; Anja Schuster (PLoS ONE, 2025)
Tree bark is a complex protective tissue that serves both physiological and defensive functions and is particularly rich in phenolic compounds bearing antioxidant, antimicrobial, anti-inflammatory and wound healing properties. The aim of this study was to investigate the antioxidant activity of aqueous bark extracts from 6 European tree species, namely black alder, common beech, silver birch, bird cherry, oak and scots pine using the antioxidant assay Antioxidant Power 1 (AOP1) on a keratinocyte cell line in the light of dermatological applications. The AOP1 assay relies on light-induced intracellular reactive oxygen species (ROS) production that disrupts efflux transport, enabling the accumulation of fluorescent cyanine dyes which can be quantitatively detected by increased fluorescence. Particular attention was placed on the multi-level output provided by AOP1, which includes information on the intracellular antioxidant as well as prooxidative effects of specific compounds and insight into the ground stress level of cells. The results showed that tree bark extracts exhibit a different antioxidant mechanism compared to the well-known antioxidative substance resveratrol. Bark extracts limit the total amount of ROS produced over the duration of the assay, with oak, beech and pine bark extracts showing the highest antioxidant capacity. In contrast, resveratrol delays ROS production over several illumination cycles before levels reach those of untreated cells. Cellular ground stress level was elevated by alder and birch whereas oak, beech and pine reduced the ground stress level similar to that of resveratrol. Results of AOP1 were linked to the constituents of the tree bark extracts derived by Soxhlet extraction, determined by HPLC-DAD analysis. The results highlight the potential of AOP1 as a screening tool with multi-level output and demonstrate the antioxidative potential of six European tree bark extracts, underscoring their promise as sustainable, value-added resources for the development of dermatological therapies targeting oxidative stress–related skin disorders.